Pemberdayaan Masyarakat Desa Bleberan Melalui Peningkatan Nilai Tambah Jagung - Anita Roosmawarni; Halimatus Sa'diyah; Adhar Putra Setiawan (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2026)
Corn is one of the agricultural sector outputs that has always been a favorite in several regions in Indonesia. Moreover, Indonesia, with its tropical climate, is a paradise for corn plants in various regions, including in Bleberan Village, Jatirejo District, Mojokerto Regency. The demographics of the Bleberan village population, as many as 11.6% work as farm/plantation laborers, supported by the still very extensive availability of land, also contribute to the increase in abundant corn harvests. The people of Bleberan Village do not yet fully understand how to increase the utility value of corn, considering that cultivation activities carried out so far are limited to personal consumption or sale in the form of raw corn. The purpose of this activity is to provide an understanding to the people of Bleberan Village about efforts that can be made to increase the economic value of corn by diversifying corn raw materials, calculating production costs incurred and measuring profits from production activities. The results obtained, the community is able to utilize corn kernels into corn crackers, adept at calculating each expected profit if this commodity is sold.